Production and characterization of recycled polycarbonate based composite material containing recycled glass fibers. Issue 4 (August 2017) - Zhu, Ping; Liu, Xiankai; Wang, Yangjun; Guan, Chuanjin; Yang, Yazheng; Zhu, Jiahao; Li, Xuheng; Qian, Guangren; Frost, Ray L.
Highlights: Recycled glass fibers and polycarbonates were reused to prepare a composite. The tensile and flexural strength of the composite increased by 73.52% and 30.43%. The properties of the composite were quite close to those of the pure product. The reinforcing mechanism of recycled glass fibers to polycarbonates was analyzed. Abstract: Nowadays, a large quantity of waste printed circuit boards (WPCBs) and waste compact discs (CDs) have been produced, which may cause secondary pollution and are a waste of resources. In this study, recycled glass fibers (RGF) from non-metals of WPCBs and recycled polycarbonate (RPC) from waste CDs were reused simultaneously to produce composites. A fourier transform infrared (FT-IR) was used to evaluate the functional groups in the modified RGF, the mechanical properties of composites was tested by an universal testing machine and scanning electron microscope (SEM) was used to determine the morphology and surface fractures of the composites. The result indicated that the RGF modified by a silane coupling agent-KH-550 improved the dispersion and compatibility of RGF particles in RPC matrix. The property of composite decreased significantly with resins decomposed during high temperature injection molding when nonmetals were as a filler to prepare a composite. Therefore, RGF in nonmetals was selected as a reinforcing filler of composites. The properties and the fracture surface morphology of the RGF/RPC composite were investigated. The results indicated that the appropriate addition of RGF in the composites can significantly improve the mechanical properties. The maximum tensile and flexural strength of the composites could reach up to 84.68 MPa and 118.3 MPa, which significantly increased by 73.52% and 30.43% respectively than those of RPC when RGF content was 40% with the particle size of 0.15–0.30 mm. The properties were quite close to those of composite which was prepared with pure GF and PC.